Sifat Fisikokimia Pati Sagu Termodifikasi dengan Metode Oksidasi Menggunakan Natrium Hipoklorit - Erka Fitria; Purwiyatno Hariyadi; Nuri Andarwulan; Ria Noviar Triana (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2018)
Indonesia has the largest sago plantation area in the world with sago flour production up to 6.84 metric ton a year. Based on this data, sago starch has the potential to be utilized as food ingredients. However, some of its physicochemical characteristics have weaknesses and become its limitation in the processing and its application on food products. Therefore, the modification process of sago starch by oxidation method could be used to change its characteristics. Oxidation was done by adding 1%, 2%, and 3% sodium hypoclorite for 30, 60, 90, and 120 minutes. Physicochemical characteristics of native and oxidized sago starch were measured for comparing their swelling power, solubility, gel strength, whiteness index, syneresis, and paste viscosity profile. The results showed that the carboxyl content increased and the amylose content decreased by the process. As compared to native sago starch, oxidation decreased swelling power capability, increased solubility, gel strength, whiteness index, also increased syneresis at the beginning of oxidation process but decreased with increasing time of oxidation and NaOCl concentration. Oxidation also affected the paste viscosity profile by increasing the pasting temperature, decreasing the peak viscosity, holding viscosity, breakdown viscosity, final viscosity, and setback viscosity. These results showed that oxidized sago starch was better physicochemical characteristic than that of native starch in term of increasing the heat and shear resistant and reducing the tendency of retrogradation.